Comparison of the Levels of the Theory of the Mind between Students with Cerebral Palsy and Healthy Students in Isfahan - Farhangi Nasab, Farahnaz; Shams, Marjan; Purpirali, Marziyeh; Yaghini, Omid (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Students suffering from cerebral palsy have fewer experiences that involve their communication and interaction as a result of their motor speech disorders compared with their healthy peers. Social cognition, specifically the theory of mind, might also be affected in these students. The purpose of this study was to investigate the states of the theory of mind in children with cerebral palsy in Isfahan city. Methods: In this study, 40 students with cerebral palsy (mean age of 10.9±1.88 years) and 40 healthy students (mean age of 10.6 1.35 years) matched for age and sex were selected by a simple non-randomized sampling method. The variables of the theory of mind were examined by a “38-question theory of mind test” and a “reading the mind in the eye test”. An independent t-test was used to compare the levels of the theory of mind between the two groups. Results: The results of this study showed that the cerebral palsy group earned lower scores than the healthy group in the 38-question tests of the theory of mind (P=0.000) and the reading the mind in the eye test (P=0.039). Conclusions: The students with cerebral palsy were at a lower level than their healthy peers in most variables of the theory of mind. So, it seems this defect is one of the problems associated with the brain damage in these students and requires more special assessments and treatments in these patients’ group. Keywords: Cerebral Palsy, Social Cognition, Theory of Mind